Services Sector in Lithuania: Labour Productivity as a Factor of Growth - Žemgulienė, Jolanta (Ekonomika, 2008)
This paper examines the tendencies of Lithuanian services sector’s value added and labour productivity during 1995-2006. Comparative analysis of the average annual labour productivity growth in manufacturing and service industries reveals arguments supporting the W. Baumol’s consideration that there can be sporadic productivity increases in nonprogressive sectors. During 1995-2000, labour productivity growth in services exceeded productivity growth in manufacturing. The paper offers an interpretation of the Verdoom law for empirical regularities of the relationship between the cross-sectorial labour productivity growth rate and the value added growth rate.